1999
DOI: 10.1074/jbc.274.27.18925
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-Retinoic Acid-mediated Growth Inhibition Involves Inhibition of Human Kinesin-related Protein HsEg5

Abstract: In this study we used differential display reverse transcription-polymerase chain reaction to search for differentially expressed all-trans-retinoic acid (ATRA)-responsive genes in pancreatic carcinoma cells. We identified the kinesin-related protein HsEg5, which plays an essential role in spindle assembly and spindle function during mitosis, as a novel molecule involved in ATRA-mediated growth inhibition. Using Northern and Western blot analysis we demonstrated that ATRA significantly inhibits HsEg5 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Further, in pancreatic carcinoma cells, the kinesin-related protein HsEg5 has been identified as a central molecule that is involved in the antiproliferative action of all-trans-retinoic acid. 19 In addition, Eg5 has been shown to be expressed more in transformed cells than in primary cells in culture. Its expression is higher in breast, colon, lung, ovary, and uterus tumors than in their adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in pancreatic carcinoma cells, the kinesin-related protein HsEg5 has been identified as a central molecule that is involved in the antiproliferative action of all-trans-retinoic acid. 19 In addition, Eg5 has been shown to be expressed more in transformed cells than in primary cells in culture. Its expression is higher in breast, colon, lung, ovary, and uterus tumors than in their adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice have shown that Eg5 expression by retroviral insertion contributes to the development of mouse B-cell leukemia (6), suggesting that Eg5 plays a role in leukemogenesis. In pancreatic carcinoma cells, the kinesin-related protein HsEg5 has been identified as a central molecule involved in the antiproliferative action of all-trans-retinoic acid (7). In addition, KSP was shown to be highly expressed in transformed cells in culture, but less so in primary cells.…”
Section: Introductionmentioning
confidence: 99%
“…A study involving another pancreatic cancer line DNA-G found that ATRA restrained cells at G2/M phase [22].…”
Section: Discussionmentioning
confidence: 99%